2021
DOI: 10.33590/emj/21-00027
|View full text |Cite
|
Sign up to set email alerts
|

Oxy-hydrogen Gas: The Rationale Behind Its Use as a Novel and Sustainable Treatment for COVID-19 and Other Respiratory Diseases

Abstract: Oxy-hydrogen gas (HHO) is a gaseous mixture of molecular hydrogen and molecular oxygen that is generated by the electrolysis of water and delivered in a 2:1 ratio (66% and 33%, respectively) through the use of noninvasive inhalation devices such as nasal cannulas or nebulisers. Although there is a paucity of scientific evidence supporting this new and emerging therapy, initial investigations indicate that HHO proffers cytoprotective qualities, typically by reducing oxidative stress and attenuating the inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Simultaneously, Erlich et al found that the excessive activation of the immune cells and persistent inflammation caused by the viral infection generate large amounts of reactive oxygen species (ROS) (10). Pro-inflammatory mediators increase the production of ROS in the mitochondria and immune cells by activating nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (11). After the virus infects the body, its replication depends on the energy metabolism of the host cells and the glycolytic pathway of the host cells is significantly enhanced, resulting in the production of a large number of ROS (12).…”
Section: Characteristics and Related Mechanisms Of The Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, Erlich et al found that the excessive activation of the immune cells and persistent inflammation caused by the viral infection generate large amounts of reactive oxygen species (ROS) (10). Pro-inflammatory mediators increase the production of ROS in the mitochondria and immune cells by activating nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (11). After the virus infects the body, its replication depends on the energy metabolism of the host cells and the glycolytic pathway of the host cells is significantly enhanced, resulting in the production of a large number of ROS (12).…”
Section: Characteristics and Related Mechanisms Of The Covid-19mentioning
confidence: 99%
“…Therefore, it may alleviate the severe pulmonary symptoms of the COVID-19 (54). Russell et al found that all the domains of life have an intrinsic biological need for hydrogen from the perspective of biological evolution and hydrogen plays a therapeutic role in a variety of respiratory diseases including the COVID-19 (11). Moreover, the COVID-19 has also been reported to induce Kawasaki-like disease, which occurs in children and leads to coronary artery damage.…”
Section: Prospectivementioning
confidence: 99%
“…In contrast, well-known antioxidants such as vitamins C (L-ascorbic acid) and E (alpha tocopherol), although effective in the short-term can accumulate in the body of susceptible individuals, leading to adverse effects including digestive distress and improper kidney or liver function if taken for a prolonged time, or in large doses [17]. As HHO is a mixture of biocompatible gases, excesses are easily eliminated from the body either by simply diffusing away, or by exhaling in our breath [18]. Such qualities make HHO an ideal therapeutic for targeting dysfunctional intracellular processes such as metabolic dysregulation and redox homeostasis, irregularities that are deemed significant to both pathogenesis and progression of menopause-associated symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…H2 gas is also endogenously produced through fermentation of nutrients by intestinal micro-organisms such as Escherichia coli [26]. Endogenous H2, however, is not found in significant quantities to be therapeutically advantageous and research shows inhalation of H2 gas to be beneficial in humans [15,18,24,25,[27][28][29][30]. To illustrate, high exposure to H2 (96%), in conjunction with 4% oxygen (O2), has been used as a treatment to prevent decompression sickness in deep-sea divers since 1944 [27].…”
Section: Discussionmentioning
confidence: 99%
“…At present, individual treatments in a medical context can include intravenous application of hydrogen-rich saline (HRS), ingestion of hydrogen-rich water (HRW), and hydrogen inhalation therapy [3], either alone or in combination with oxygen (O 2 ), in a mixture referred to as oxy-hydrogen (HHO) [5]. Topical and hyperbaric application of H 2 has also been demonstrated to have salutary effects on conditions such as soft tissue injury [6], decompression sickness [7], and cancer [8].…”
Section: Introductionmentioning
confidence: 99%